The Language of Emotions : Conceptualization, expression, and theoretical foundation. - Niemeier, Susanne (John Benjamins Pub. Co., 1997)
Since the celebration of the 100th anniversary of Darwin's The Language of the Emotions in Man and Animals (1872), emotionology has become a respectable and even thriving research domain again. The domain of human emotions is most important for mankind, emotions being right in the center of our daily lives and interests. A key-role in the interdisciplinary scientific debate about emotions has now been accorded to the study of the language of emotions. The present volume offers a new approach to the study of the language of emotions insofar as it presents theories from very different perspective.